The EU's inescapable influence on global regionalism - Lenz, T (2012)
This thesis examines the EU's influence on regional cooperation in the Association of Southeast Asian Nations (ASEAN), Mercosur in South America and the Southern African Development Community (SADC) by drawing on concepts from diffusion studies. It argues that conventional perspectives have tended to view different cases of regionalism as independent phenomena reflecting particular structural, institutional or ideational conditions, mainly internal to the respective region itself. I propose instead to conceive of regional organisations as asymmetrically interdependent, in that the EU as the most successful regional grouping in the international system influences other regional organisations in important respects; yet in ways that are ill-captured by the conventional depiction of external influence as a form of coercion. The central question addressed in this thesis is thus: Under what conditions and in what ways does the EU affect the trajectory of formal rules in regional cooperation elsewhere? I advance three main arguments. First, I suggest that given the EU's ideational and material power in global regionalism, it is likely to act as a focal point in debates about regional rule change around which actors' expectations converge when being confronted with an exogenous cooperation problem. This renders EU influence difficult to escape. Second, I argue that there are two dynamics by which EU influence affects outcomes in global regionalism - the EU as switchman and as driver. While the former leads policy-makers to choose EU-type rules instead of similarly viable alternatives given a particular cooperation problem, the latter affects the very incentives for regional rule change and thereby acts as an independent driver of regional cooperation. Third, I argue that, in terms of outcomes, EU influence has been highest in SADC, lower in Mercosur and lowest in ASEAN, mainly reflecting different degrees of material and ideational interdependence between the EU and other regions. Yet, policy-makers' widespread reluctance to share national sovereignty has sharply delineated the boundaries of EU influence in all three regions. I test these arguments across three central areas of regional cooperation: market building, institution building and community building.